(3QLGd GdTjN GHf OGhOs - (3GdMdj, GHf OGhO, CHh eMeO, Jbj GdOjf, GdMSf Hf Ydj Hf OGhO, (B740 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEfj deG fXQJ aj CUhd GdaJGhi GdabgjI haQhYgG GdfXQjI hMGhdJ GdNdGU ef GdTHgGJ GdJbdjOjI hGJHGY eG fTCJ Ydjg ef GdaJGhi GdeMcjI GVWQQJ Edi SHQ GdGMGOjK GdeQhjI (B...s
(3BNQgG (B:s
... (3CeG GdcGaj agh JCdja KbI GdESdGe CHj LYaQ eMeO Hf jYbhH Gdcdjfj GdQGRj (B...(3YOg LeGYI ef YdeGA GdYGeI cGHf GdCKjQ aj cJGH LGeY GdCUhd ef GdeLOOjf dePgH (B...s
(3JHUQI GdYfhGf (B:s
(3hjSei cTa GdebGd aj eYQaI CMhGd GdQLGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B2/204s
(3GdPQjYI (B10 - 64 ( 155)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs